INITIAL ASSESSMENT OF TREATMENT RESULTS FOR ERECTILE DYSFUNCTION USING THE ED60 MAGNETIC DEVICE (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical and paraclinical characteristics and evaluate the initial treatment outcomes of erectile dysfunction using the ED60 magnetic device.Methods: A prospective descriptive study without a control group was conducted on 38 patients with erectile dysfunction. Initial treatment outcomes were assessed using the IIEF-5 score before and after intervention. Data were analyzed using statistical software with mean, standard deviation, and paired t-test, with a significance level of p < 0.05.Results: After treatment, the IIEF-5 score significantly increased from 9.47 ± 2.75 points to 12.45 ± 2.55 points (p < 0.001). Improvement was observed across all age groups. The majority of patients reported acceptable or satisfactory outcomes following treatment.Conclusion: Treatment with the ED60 magnetic device showed an initial improvement in IIEF-5 scores and no recorded complications during the short follow-up period. However, because this study had no control group, a small sample size, and limited follow-up duration, larger controlled studies are needed to confirm long-term effectiveness.
Keywords: Erectile dysfunction, ED60, magnetic therapy, non-invasive treatment, IIEF-5, initial outcomes.